Uma aplicação da álgebra de Clifford para o ensino da Teoria da Relatividade Restrita - Camêlo, Bruno Barros (2014)
In physics is very familiar employment of vectors. These can be seen, the geometric point of view, as straight segments oriented. However, certain quantities are better represented by other objects with geometrical features than with vectors. Such objects are represented by fragments of oriented planes, which cannot be determined by vectors, unless we are in three dimensional space. Geometric or Clifford algebra can be treated as a generalization of vector algebra, and consists of a powerful formalism for the physical description of nature. Thus, we propose in this work, to build strategies to introduce the Clifford algebra as modeler physical concepts of the Theory of Special Relativity and from the modeled concepts, develop educational material for teaching physics in the light of the conception of learning Ausubel.